East China Sea ecosystem under multiple stressors: Heterogeneous responses in the sea surface chlorophyll-a. (September 2019) - Kong, Christina Eunjin; Yoo, Sinjae; Jang, Chan Joo
Abstract: The East China Sea and southern Yellow Sea ecosystems have undergone drastic changes over the past decades. The changes in the ecosystems are attributable to both natural and anthropogenic stressors. We analyzed the seasonal and interannual variability of the sea surface chlorophyll-a in the East China Sea and the southern Yellow Sea using a suite of remotely sensed data (1998–2012). When seen on a Large Marine Ecosystem level, there seems no trend in the region. However, when seen on a sub-regional scale, heterogeneous responses can be recognized among the subregions. There was an increasing trend of chlorophyll-a in the vicinity of the Changjiang (Yangtze) River mouth, while there was a decreasing trend in the southeastern slope area which can be attributed to anthropogenic nutrient enrichment and warming, respectively. Contrary to some previous studies, our analysis clearly showed that the summer-autumn averaged chlorophyll-a decreased by about 14% in a large area (circa 178, 000 k m 2 ) in the northeastern East China Sea after 2003 coinciding with the initial impoundment of the Three Gorges Dam. Our analysis demonstrates that our ability to detect the trends in response to multiple stressors largely depends on choosing an appropriate spatiotemporal scale. Highlights: The East China Sea ecosystem has undergone spatio-temporally heterogeneous changes. In nearshore areas, the chlorophyll-a increased due to anthropogenic nutrient enrichment. In the continental slope areas, the chlorophyll-a gradually decreased due to warming. The chlorophyll-a in an offshore area was reduced after the Three Gorges Dam operation. Choosing an appropriate scale is vital to unravel heterogeneous ecosystem responses.